1980
DOI: 10.1007/bf03189464
|View full text |Cite
|
Sign up to set email alerts
|

Structural parameters in the microsomal hydrolysis of 3-acyloxy-l, 4-benzodiazepines and the multiplicity of the esterases involved

Abstract: The biotransformation of several prodrug-type esters of centrally acting 1, 4-benzodiazepines was studied. Their rates of hydrolysis catalyzed by the hepatic microsomal fraction of mice were measured by pH-stat. The heterogeneity of the microsomal esterases was investigated with induction by phenobarbital and with inhibition by DFP. The resulting changes in esterase activity indicated that the phenyl-substituted esters separate from the homogenous sets of oxazepam and lorazepam esters. Regression analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Their behavior towards modulators of esterase activity suggested that they were a heterogeneous group of enzymes, in accord with the heterogeneity known of other esterases such as hepatic esterases (25). For the time being, two of the possible members in this group could be acetylcholinesterase and pseudocholinesterase.…”
Section: Resultsmentioning
confidence: 80%
“…Their behavior towards modulators of esterase activity suggested that they were a heterogeneous group of enzymes, in accord with the heterogeneity known of other esterases such as hepatic esterases (25). For the time being, two of the possible members in this group could be acetylcholinesterase and pseudocholinesterase.…”
Section: Resultsmentioning
confidence: 80%